High NOTCH1 mRNA Expression Is Associated with Better Survival in HNSCC - Wirth, Markus (Int J Mol Sci, 2018)
The clinical impact of the expression of NOTCH1 signaling components in squamous cell carcinoma of the pharynx and larynx has only been evaluated in subgroups. The aim of this study was therefore to evaluate NOTCH1 expression in head and neck squamous cell cancer (HNSCC) patient tissue and cell lines. We analyzed tissue from 195 HNSCCs and tissue from 30 normal patients for mRNA expression of NOTCH1, NOTCH3, HES1, HEY1, and JAG1 using quantitative real-time PCR. Association of expression results and clinical orpathological factors was examined with multivariate Cox regression. NOTCH1 expression was determined in three Human Papilloma Virus (HPV)-positive and nine HPV-negative HNSCC cell lines. High expression of NOTCH1 was associated with better overall survival (p = 0.013) and disease-free survival (p = 0.040). Multivariate Cox regression confirmed the significant influence of NOTCH1 expression on overall survival (p = 0.033) and disease-free survival (p = 0.029). A significant correlation was found between p16 staining and NOTCH1 mRNA expression (correlation coefficient 0.28; p = 0.01). NOTCH1 was expressed at higher levels in HPV-positive HNSCC cell lines compared with HPV-negative cell lines, which was not statistically significant (p = 0.068). We conclude that NOTCH1 expression is associated with overall survival, and that inhibition of NOTCH1 therefore seems less promising.